Penerapan Model Pembelajaran Cooperative Learning Untuk Meningkatkan Hasil Belajar Seni Tari Kelas X DKV di SMK Teknologi Plus Padang - Susmiarti Susmiarti; Isbaniyah Syafitri P. (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe the application of the Cooperative Learning Model Can Improve the Learning Outcomes of Class X Students of DKV SMK Teknologi Plus Padang. This type of research is classroom action research. This research was carried out in 2 cycles with the stages of planning, implementation, observation, and reflection. Data were collected through observation, literature studies, tests and documentation. The data was analyzed using a percentage formula. The results of the study show that the Cooperative Learning learning model with teachers as a direct example can improve learning activities and student dance learning outcomes. The average percentage of student learning activities in the first cycle was 58.5% with the criteria of Not Good. After making improvements in the second cycle, the average student learning activity became 86% with good criteria. Students who were previously less enthusiastic and only silent when moving become active, students who are shy in making movements become confident, students who disturb other students and just play become serious or focused in doing the assigned tasks, students who help each other when experiencing difficulties when practicing with a group. The use of the Cooperative Learning learning model in dance learning in class X DKV also has an impact on the average student learning outcome score. The average score of completeness of student learning outcomes in cycle I was 37.5%. Because it has not reached the KKTP, which is 75, it was carried out again in the second cycle and managed to reach a score of 87.5%.